2008
DOI: 10.1007/s10666-008-9152-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a General Finite Line Source Model and CALINE4 for Vehicular Pollution Prediction in Ireland

Abstract: A comparative evaluation of two Gaussian-based line source models namely, California line source dispersion model version 4 and the general finite line source model, is presented. The concentrations predicted by these models are compared with background-corrected ambient concentrations measured at three different distances from a motorway and performance of both models assessed in the context of integrated transport-environment modelling for regulatory purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Ganguly and Broderick (2008) found a reasonable level of agreement between the CALINE results and measurements based on graphical and statistical analysis. Ganguly et al (2009) found that the model was in good accordance to in situ measurements. Broderick et al (2005) validated the model for CO with results within ± 50% of the measurements.…”
supporting
confidence: 68%
“…Ganguly and Broderick (2008) found a reasonable level of agreement between the CALINE results and measurements based on graphical and statistical analysis. Ganguly et al (2009) found that the model was in good accordance to in situ measurements. Broderick et al (2005) validated the model for CO with results within ± 50% of the measurements.…”
supporting
confidence: 68%
“…: non-steady wind flow/disturbed air flow, street canyon, elevated inversion conditions near enough to surface to influence the surface concentration, low wind speeds, estimation of photochemical pollutant, and adjacent to interchange or intersection (Levitin et al, 2005;Broderick et al, 2006;. CALINE4 model often considered as a reference model against which various other atmospheric models are tested (Ganguly et al, 2009). According to Méline et al (2011), CALINE4 is considered suitable for modelling air pollution in fairly flat terrain (Pitts, 2004).…”
Section: Brief Description Of Caline4 Modelmentioning
confidence: 99%
“…The study reported under-performance by CALINE4 and IILTS model in comparison to linear regression model(s). Further, Ganguly et al (2006) compared the performance of GFLSM to that of CALINE4 model. The study was aimed to predict speciated hydrocarbon, NO x and CO.…”
Section: Performance Evaluation and Comparative Assessment Of Caline4mentioning
confidence: 99%
See 1 more Smart Citation
“…Bhanarkar et al [12] assessed the SO 2 and NO 2 pollution level in Jamshedpur region by ISCST3 model and observed that predicted 24-h concentrations have good agreement with measured concentrations at 11 ambient air monitoring stations. Ganguly et al, [13] had used two models CALINE 4 and GFLSM [14] and done comparative evaluation. Further, the commercial available air quality models e.g.…”
Section: Introductionmentioning
confidence: 99%